Healthy work: evidence into action - Vaughan-Jones, Helen; Barham, Leela (London, 2010)
"Healthy Work: Evidence into Action shows how improved workplace health can make a significant contribution to the economy, to public finances and to reducing levels of illness and disease in the UK. It is the final report of Bupa’s health at work project, which has been carried out in partnership with The Work Foundation, C3 Collaborating for Health (working with The Oxford Health Alliance) and RAND Europe. The first report of the project, called Healthy Work: Challenges and Opportunities to 2030, looked at how trends in the demography and economy of the UK and patterns of disease will affect the health of the workforce over the next 20 years.'